Integration and Law : the Irish experience in its international and European context - Murphy, Clíodhna Siobhán (Trinity College (Dublin, Ireland). School of Law, 2012)
This thesis examines the interaction between integration and law, from an Irish perspective. It explores the legal dimensions of the concept of integration and its coherence in a European and international context. It examines the legal and policy framework for the integration of migrants that is being constructed in Ireland and critically discusses the multiple paradigms of integration that are influencing the development of this framework. In particular, by analysing the approaches of the United Nations (human rights). Council of Europe and European Union systems, the thesis considers the actual and potential impact of these systems on Irish law and policy on integration. The thesis is structured in three parts. The first part addresses the meaning of "integration" and the nature of its relationship with law. It presents an in-depth analysis of the policy framework for integration in Ireland, in light of the definitions of integration developed by the Council of Europe, the EU and UNHCR. This part of the thesis also considers in detail the various dimensions of the relationship between integration and law, and the factors which may shape this engagement. The second part of the thesis analyses the legal foundations of integration at the international, EU and national levels. In the sphere of international law, a nascent integration paradigm as the progressive realisation of equality is identified in the work of the UN human rights treaty monitoring bodies. The role of the concept of integration in the jurisprudence of the European Court of Human Rights is also outlined. So too the conflicting concepts of integration evident in EU law and policy are discussed. In the sphere of Irish law, the Irish constitutional framework for integration is analysed by looking at both the values underlying the text of the Constitution and the interpretation of the fundamental rights provisions by the Irish courts in cases involving immigration. The third part of the thesis examines a number of discrete areas of Irish law with strong links to integration, including citizenship, family reunification and the state's relationship with religion, as a means to consider the relationship between integration and law in the Irish setting.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin